Evolving Perception Regarding Online Learning and Teachingin the COVID-19 Era of Graduate Students with diverse educational backgrounds enrolled inMaster’s Health Professional Education Program of a Pakistani University - Nadeem, Amina; Rashid, Azhar; Yasmeen, Rahila (Pakistan Armed Forces Medical Journal, 2023)
Objective: To analyze the evolving perception of graduate students of Masters in ‘health professional education with diverse educational backgrounds regarding online learning and teaching. Study Design: Mixed-method’ study of Convergent Parallel Design. Place and Duration of Study: Riphah University, Rawalpindi Pakistan, Dec 2021 to Feb 2022. Methodology: Twenty-five graduate students of Masters in ‘health professional education’ with diverse educational backgrounds answered semi-structured questionnaires at the end of 2 online teaching sessions. Results: The mean scores of 3 domains of ‘student’s perception of learning, ‘contents and teaching strategies and ‘educational environment’ in 1st vs second online sessions were as follows, respectively: (4.37 0.42 vs 4.09, 0.45; p-value 0.04), (4.40 0.47 vs 4.29, 0.58; p-value 0.44) and (4.43 0.43 vs 4.23 0.69; p-value 0.36). The students agreed that the contents covered, teaching strategies and education environment were satisfactory, and the perception was not statistically different between the two sessions in these domains. In contrast, students’ self-perception of learning was more satisfactory in the first online session. Conclusion: The graduate students of Masters in ‘health professional education’ with diverse educational backgrounds were satisfied regarding the contents covered, teaching strategies and education environment in two online teaching sessions. In contrast, their perception of their learning depreciated in the second online teaching session.